Perancangan Sistem Keamanan Motor Dengan Menggunakan State Machine - Arycca Septian Mulyana; Wijaya Kurniawan; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Based on data obtained from BPS (Statistics Indonesia) regarding motorcycle theft cases in Indonesia shows an increase in each year. So that makes people become more worried about the safety of two wheeled vehicles. There are many security systems of two-wheeled vehicles that have been circulating in Indonesia, but the price offered relatively expensive, thus making people reluctant to use it. To that end, the authors have made the design of motorcycle security system by using a State machine that utilizes multiple sensors and existing technologies. The sensor used is a fingerprint sensor and GPS sensor, coupled with some technology in the form of data transmission using SMS-Gateway. The fingerprint sensor is used to detect fingerprints from vehicle users, GPS as location readings and notices when two-wheeled vehicles move while parked, and SMS-Gateway as a location data transmission medium and two-wheel drive notification. In making the program will be used State machine as the method. Finite state machine has three basic elements, namely State, Event and Action. Based on the results obtained from testing on the system, it can be concluded with the existence of this system the safety level of the motor can increase, and the time obtained in the delivery and reception of data is relatively efficient or brief and the use of state machine on the system can run well.